1993
DOI: 10.1002/art.1780361117
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory polyarthritis in mice transgenic for human t cell leukemia virus type i

Abstract: Objective. We have recently reported that arthropathy develops in high incidence among transgenic mice carrying the pX region of human T cell leukemia virus type I (HTLV-I). In the present study, the histopathologic features of the joints in these mice were examined in order to compare the animal disease with rheumatoid arthritis (RA) in humans.Methods. Paraffin sections of limbs (right and left fingers, wrists, elbows, shoulders, toes, knees, and ankles) were stained with hematoxylin and eosin, periodic acida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…This protein transactivates not only the viral long terminal repeat but also a variety of cellular genes, including interleukin-2 (IL-2), IL-2 receptor (IL-2 R), or other lymphokines (23)(24)(25). Thus, the transgenic mice carrying the HTLV-I tax genomes show chronic arthritis including erosive destruction of the bone, pannus formation, and lymphocytes infiltration resembling RA (11,12). Moreover, recent studies by Iwakura et al (13) demonstrated that the transgenic mice carrying HTLV-I env-tax region not only produce high levels of antibodies against IgG, collagen type II (IIC), heat shock protein (Hsp), and DNA, but also provide T cell proliferation to IIC and Hsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein transactivates not only the viral long terminal repeat but also a variety of cellular genes, including interleukin-2 (IL-2), IL-2 receptor (IL-2 R), or other lymphokines (23)(24)(25). Thus, the transgenic mice carrying the HTLV-I tax genomes show chronic arthritis including erosive destruction of the bone, pannus formation, and lymphocytes infiltration resembling RA (11,12). Moreover, recent studies by Iwakura et al (13) demonstrated that the transgenic mice carrying HTLV-I env-tax region not only produce high levels of antibodies against IgG, collagen type II (IIC), heat shock protein (Hsp), and DNA, but also provide T cell proliferation to IIC and Hsp.…”
Section: Discussionmentioning
confidence: 99%
“…We administrated anti-Fas mAb (RK-8) to human T cell leukemia virus type I (HTLV-I) 1 tax transgenic mice. HTLV-I tax transgenic mice is considered to be one of the most suitable models for human RA, since these animals develop chronic synovitis and an immunological disorder resembling human RA (11)(12)(13). Our results demonstrated that intra-articular administration of anti-Fas mAb in these mice improved the paw swelling and histologic features of arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Nerenberg (1990) described neurofibromas in HTLV-1 promoter (LTR)-Tax transgenic mice and used antisense inhibition of NF-kB to demonstrate its role in tumor growth. Lymphocytemediated arthropathy developed in Tax transgenic mice controlled through the HTLV-1 promoter (Iwakura et al, 1991(Iwakura et al, , 1995Yamamoto et al, 1993;Fujisawa et al, 1996). Increased levels of nerve growth factor, granulocyte-macrophage colony-stimulating factor (GM-CSF) and IL-2 receptor also developed in transgenic mice in which Tax was expressed from the human granzyme B promoter (GzmB) (Grossman and Ratner, 1997).…”
Section: Transgenic Modelsmentioning
confidence: 99%
“…Genetically engineered mice expressing the tax gene of HTLV-I develop symptoms resembling Sjögren's Syndrome (SS) (Green et al, 1989). Transgenic mice expressing parts of the HTLV-I env and tax genes developed chronic inflammatory arthropathy resembling rheumatoid arthritis (Iwakura et al, 1991;Yamamoto et al, 1993). SS (autoimmune exocrinopathy) is among the systemic autoimmune diseases that share clinical symptoms with diseases induced by HIV.…”
Section: Introductionmentioning
confidence: 99%